Impact of Autophagy and Aging on Iron Load and Ferritin in Drosophila Brain - Jacomin, Anne-Claire; Geraki, Kalotina; Brooks, Jake; Tjendana-Tjhin, Vindy; Collingwood, Joanna F.; Nezis, Ioannis P. (Frontiers in Cell and Developmental Biology, 2019)
Biometals such as iron, copper, potassium, and zinc are essential regulatory elements of several biological processes. The homeostasis of biometals is often affected in age-related pathologies. Notably, impaired iron metabolism has been linked to several neurodegenerative disorders. Autophagy, an intracellular degradative process dependent on the lysosomes, is involved in the regulation of ferritin and iron levels. Impaired autophagy has been associated with normal pathological aging, and neurodegeneration. Non-mammalian model organisms such as Drosophila have proven to be appropriate for the investigation of age-related pathologies. Here, we show that ferritin is expressed in adult Drosophila brain and that iron and holoferritin accumulate with aging. At whole-brain level we found no direct relationship between the accumulation of holoferritin and a deficit in autophagy in aged Drosophila brain. However, synchrotron X-ray spectromicroscopy revealed an additional spectral feature in the iron-richest region of autophagy-deficient fly brains, consistent with iron–sulfur. This potentially arises from iron–sulfur clusters associated with altered mitochondrial iron homeostasis.